ANALISIS KELANCARAN DISTRIBUSI PAKAN UNGGAS DI KABUPATEN LIMA PULUH KOTA PROVINSI SUMATERA BARAT PADA MASA PANDEMI COVID-19 - Adli Putra Ermanda; Nita Adillah Pratiwi (Journal Agro-Livestock, 2023)
Since the COVID-19 epidemic broke out in Indonesia, the government of the Republic of Indonesia enacted the PSBB (Large-Scale Social Restrictions) policy on March 31, 2020, which restricts people's ability to engage in outdoor activities and impedes economic activity, particularly the livestock industry. The distribution of animal feed components during the PSBB was hampered by the supply of animal feed ingredients in West Sumatra region, which is still fulfilled from outside the region. 50 farmers were interviewed for this study during the implementation of the PSBB policy, and the data gathered included an observation of the variable smoothness of the transportation of poultry feed ingredients. 74% of respondents said that this transportation was smooth before the PSBB, but that smoothness decreased by up to 56% during implementation of the PSBB policy in Limapuluh Regency. City, West Sumatra Province.